Shoot to Kill : Why We Hunt - O'Dell, Kathryn (NewYork Cambridge University, 2014)
People hunt for food, but they also hunt for other reasons. This reader explores the different types and purposes of hunting, uncovering the wide variety of attitudes and perspectives surrounding this age-old practice
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Elementary level